Acute Kidney Injury and Fluid Overload in Neonates Following Surgery for Congenital Heart Disease. (July 2015) - Piggott, Kurt D.; Soni, Meshal; Decampli, William M.; Ramirez, Jorge A.; Holbein, Dianna; Fakioglu, Harun; Blanco, Carlos J.; Pourmoghadam, Kamal K.
Background: Acute kidney injury (AKI) and fluid overload have been shown to increase morbidity and mortality. The reported incidence of AKI in pediatric patients following surgery for congenital heart disease is between 15% and 59%. Limited data exist looking at risk factors and outcomes of AKI or fluid overload in neonates undergoing surgery for congenital heart disease. Methods: Neonates aged 6 to 29 days who underwent surgery for congenital heart disease and who were without preoperative kidney disease were included in the study. The AKI was determined utilizing the Acute Kidney Injury Network criteria. Results: Ninety-five neonates were included in the study. The incidence of neonatal AKI was 45% (n = 43), of which 86% had stage 1 AKI. Risk factors for AKI included cardiopulmonary bypass time, selective cerebral perfusion, preoperative aminoglycoside use, small kidneys by renal ultrasound, and risk adjustment for congenital heart surgery category. There were eight mortalities (five from stage 1 AKI group, three from stage 2, and zero from stage 3). Fluid overload and AKI both increased hospital length of stay and postoperative ventilator days. Conclusion: To avoid increased risk of morbidity and possibly mortality, every attempt should be made to identify and intervene on those risk factors, which may be modifiable or identifiable preoperatively, such as small kidneys by renal ultrasound.